A lyophilised formulation of chimpanzee adenovirus vector for long-term stability outside the deep-freeze cold chain - Frédéric Mathot; Edwige Lefebvre; Bernard G. Francq; Delphine Guillaume; Erwan Bourlès (Communications Medicine)
Abstract Background The adenovirus-vaccine platform has come to prominence with the COVID-19 vaccination campaigns. The objective of this study was to validate a formulation that was suitable for lyophilisation and long-term storage at 5 (2–8) °C. Methods Vaccine stability was assessed up to five years at 5 °C using a lyophilised formulation of the chimpanzee-adenovirus vector ChAd155 encoding a respiratory syncytial virus (RSV) antigen. Vaccine potency was assessed by functional infectivity assay. Other assessments of vaccine stability included those for capsid integrity, particle content, and DNA release. Vaccine efficacy and safety were assessed after two years in a murine model of RSV challenge and a rabbit toxicology model, respectively. Results Here, we show that the potency loss from lyophilisation was 0.12 log10. The potency loss over five years at 5 °C was estimated at 0.21 log10 (95%CI 0.10–0.30). This coincides with a 25% increase in the ratio of non-infectious particles/infectious particles. After two years of storage at 5 °C, (i) the loss of infectivity was 0.17 log10; (ii) the vaccine remained immunogenic and effective at clearing RSV from the lungs in a mouse-challenge model; and (iii) the vaccine was not associated with any adverse safety signal in a rabbit toxicology model. Conclusions The 5-year stability of the lyophilised adenovirus-vector vaccine is within our acceptable limit ( < 0.3 log10 decrease). Its formulation process is amenable to manufacturing scale-up and should help in providing adenovirus-based vaccines where the cold chain is problematic, such as in low-income countries, and in pre-epidemic stockpiling.